ANALISIS PERBEDAAN KINERJA SAHAM JANGKA PENDEK DAN JANGKA PANJANG PADA PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFRERING (IPO) DI PASAR MODAL INDONESIA - Mg. Kentris Indarti; Kartika Andi; Yohanes Yohanes (Jurnal Bisnis dan Ekonomi, 2004)
The objective of this study is to find empirical evidence about presupposition that underpricing and underperformance phenimenons occurs on companies issued Initial Public Offering (IPO) in Indonesia. There are 36 companies that issued IPO during 1998-2000. After choosing then with purposive sampling method, there are 33 companies to be analyzed in this study. Results from one sample t-test show that in the short run, there are large positive mean excess return. This result is consistent with prior studies in numerous countries. In the long run, the perfomance is underperformed. Result from paired sample t-test show that there is a significant defference between short and long run stock performance in companies issued IPO.Key words: Initial Public Offering, Performance, Underpricing, Underperfomed